Karakter Percabangan Malai Genotipe Padi Sawah pada Berbagai Level Dosis Fosfor - Hastini, Tri; Suwarno, Willy Bayuardi; Ghulamahdi, Munif; Hajrial, dan Aswidinnoor (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Yield grain of rice was determined by genetical and environmental factors, one of them was genetic response on levelof phosphorus. Rice panicle branching was one of the key factors on supporting rice yield. The study aimed to find out ricepanicle branching responses to phosphorus. Controlled experiment was conducted on September 2017 - February 2018, usingtwo genotypes planted on poor soil media and six levels of phosphorus as treatments, arranged in completely randomizeddesign. Panicle branching characters were observed on the experiment. The experiment showed the genotype’s effects atall panicle branching except number of tertiary branches and number of grains on tertiary branches. Phosphorus affectedpanicle branching except panicle length, primary branch length, and number of grain on tertiary branches. Genotype andphosphorus interaction appeared at all panicle branching except number of primary branch, number of tertiary branches,number of grains on tertiary branches, and the percentage of grains number on tertiary branches. The panicle of genotypeIPB180-12 was likely more stabil to the various levels of phosphorus, meanwhile the panicle of genotype IPB158-5 moresensitive. According to the polynomial regression evaluation, the optimum level of P2O5 for the sensitive genotype was 421.92kg ha-1, and for the tolerant genotype was 108 kg ha-1 in poor soil.